PRIMARY AND SECONDARY IMMUNE RESPONSE TO FORMALIN INACTIVATED STREPTOCOCCUS AGALACTIAE ISOLATES IN RABBITS - M. ABUBAKAR, G. MUHAMMAD1 AND K. IBRAHIM (Pakistan Veterinary Journal, 2006)
The present study was conducted to evaluate primary and secondary immune response to formalin inactivated Streptococcus agalactiae isolates in rabbits. Streptococcus agalactiae was isolated from mastitic buffaloes. The organism was characterized on the basis of morphological, cultural and biochemical tests. An increased geomean antibody titer was observed in rabbits inoculated with single dose (Group A) and double dose (Group B) of Streptococcus agalactiae antigen. It was also evident from the results that the double dose of Streptococcus agalactiae antigen in rabbits (Group B) showed better and long lasting humoral antibody response as compared to single dose (Group A).